Twisted planes - Guccione, Jorge Alberto (2010)
Let k be a commutative ring. We find and characterize a new family of twisted planes (i.e., associative unitary k-algebra structures on the k-module k[X, Y], having k[X] and k[Y] as subalgebras). Similar results are obtained for the k-module of two variables power series k[[X, Y]].